(untitled) (Colombia Medica, 2011)
Introduction: Infection by Mycoplasma pneumoniae is becoming more frequent at younger ages. It appears as a generally benign and unspecific clinical condition of respiratory symptoms and sometimes responsible for a broad spectrum of extrapulmonary manifestations. Objective: To describe demographic, clinical, laboratory, and treatment characteristics of pediatric-age patients with positive serology for M. pneumoniae diagnosed at the Pablo Tobón Uribe Hospital (HPTU) during the 2006-2008 period. Materials and methods: Observational, retrospective study, which describes the demographic, clinical, laboratory, and treatment characteristics of patients from 1 month to 14 years of age with positive IgM for M. pneumoniae seen at HPTU during September 2006 and November 2008. Results: We reviewed 305 clinical charts of patients with positive IgM for M. pneumoniae. The average age was 5.15 years ± 3.62 SD. Cough (87.5%), fever (65.9%), rhinorrea (39.3%), and respiratory difficulty (38%) were the most frequent clinical findings. Extrapulmonary compromise was mainly manifested in the skin (12.8%), the central nervous system (CNS) (3.6%), and osteomuscular system (3.9%). Auscultation and thoracic X-ray were normal in 33.1% and 30.8% of the patients, respectively. Episodes of asthma exacerbation were related to infection by Mycoplasma in 35% of the cases. A total of 51% of the patients required hospitalization with an average stay of seven days. All the patients received antibiotic treatment; clarithromycin (75.8%) was the antibiotic of choice. Conclusion: Infection by M. pneumoniae has a broad range of clinical manifestations, requiring a high index of clinical suspicion and an active search for extrapulmonary compromise given that in our realm there is no specific diagnostic method for the acute infection.